The Relationship Between Respondents’ Characteristics and Nurses’ Burnout in Caring Covid-19 Patients - Hutapea, Adventina Delima; Risnawati, Risnawati; Trisnawati, Trisnawati; Tahulending, Peggy Sara (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Covid-19 causes fear, worry, fatigue, and post-traumatic stress disorder in nurses who are frontline staff in hospitals.  Based on a survey at a hospital nurses felt burnout in caring for the covid-19 patients due to lack of rest, lack of concentration when providing nursing care, and physical burnout caused by an increase in patients with COVID-19. This study aims to determine the association between respondent characteristics and nurses’ burnout while in caring for covid-19 patients.This research used a correlation quantitative research design with a cross-sectional approach.  The sampling technique used was a total sampling of 52 nurses who work at private hospitals in western Indonesia.  Data analysis was bivariate with the Pearson chi-square test.  The research questionnaire used a subjective questionnaire self-rating test from the industrial fatigue research committee Japan (IFRC). The chi-square test resulted that the variables were not related in caring for covid-19 patients, which is age (p-value = 0.414), gender (p-value = 0.404), education (p-value = 0.069), and marital status (p-value = 0.429). Burnout can occur from several factors such as workload, shift, and work environment. This result can imply for nurses to arrange a time to rest and better scheduling. Nursing managers can also reduce burnout by rewarding, motivating, foster a sense of community in the workplace, and creating a comfortable environment for nurses. Keywords: Burnout, Nurse, Fear, Stress Disorder, Post-Traumatic, Covid-19